2015
DOI: 10.18632/oncotarget.3587
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal adenocarcinoma and obesity: peritumoral adipose tissue plays a role in lymph node invasion

Abstract: Obesity is associated with cancer risk in esophageal adenocarcinoma (EAC). Adipose tissue directly stimulates tumor progression independently from body mass index (BMI), but the mechanisms are not fully understood. We studied the morphological, histological and molecular characteristics of peritumoral and distal adipose tissue of 60 patients with EAC, to investigate whether depot-specific differences affect tumor behavior. We observed that increased adipocyte size (a hallmark of obesity) was directly associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 52 publications
3
47
0
2
Order By: Relevance
“…These include differentiation into cancer-associated myofibroblasts (CAFs), paracrine signaling, secretion of adipokines that promote vascularization and creation of an inflammatory microenvironment [41]. Moreover, reports have found that ASCs isolated from obese humans or animals increase tumorigenesis to a greater extent than cells from normal weight individuals, typically displaying increased expression of adipokines, chemokines and/or matrix metalloproteinases [37][38][39][40]42]. As others have shown, we found ASC viability to be inversely correlated with BMI [43].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These include differentiation into cancer-associated myofibroblasts (CAFs), paracrine signaling, secretion of adipokines that promote vascularization and creation of an inflammatory microenvironment [41]. Moreover, reports have found that ASCs isolated from obese humans or animals increase tumorigenesis to a greater extent than cells from normal weight individuals, typically displaying increased expression of adipokines, chemokines and/or matrix metalloproteinases [37][38][39][40]42]. As others have shown, we found ASC viability to be inversely correlated with BMI [43].…”
Section: Discussionsupporting
confidence: 70%
“…Despite the beneficial role of ASCs in cell-based therapies, ASCs have also been implicated in tumor development or progression [36][37][38][39][40]. Several mechanisms have been proposed to explain how ASCs interact with cancer cells and affect their microenvironment [41].…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma in the lower part of esophagus most often arises from the epithelium of intestinal metaplasia (Barrett’s); while squamous cell carcinoma occurs mainly in the middle and lower regions and originates from non-keratinized stratified epithelium [100]. In a study of esophageal adenocarcinoma increased peri-tumoral adipocyte size was associated with higher leptin expression, angiogenesis, lymphangiogenesis and nodal metastasis [101]. These findings suggest that leptin secreted from peri-tumoral adipocytes may play a key role in the progression of cancer.…”
Section: Leptin and Tumor Behavior Of The Gastrointestinal Tractmentioning
confidence: 99%
“…In a previous study, we reported that the altered expression of leptin and adiponectin, secreted by adipose tissues in ESCC, correlated with lymph node metastasis and advanced tumor stage [19] . Furthermore, a recent study revealed that peritumoral adipose tissue may exert a direct effect on the progression and lymph node invasion of EAC by secreting depot-specific paracrine factors, and that leptin is a key player in this crosstalk [20] .…”
Section: Discussionmentioning
confidence: 99%